2015
DOI: 10.1016/j.cbpa.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Baseline defense system of commercial male king crab Lithodes santolla from the Beagle Channel

Abstract: Environmental and physiological variations influence the steady-state concentration of free oxygen radicals in cells. Because of the seasonal life cycle of Lithodes santolla in the Beagle Channel, a baseline study of the antioxidant physiological variations along the seasons is necessary for a better understanding of its ecophysiology. The aim of this study was to evaluate the seasonal variations in gills, hemolymph, muscle and hepatopancreas of the: i) enzymatic activities of superoxide dismutase, catalase, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 158 publications
(275 reference statements)
0
3
0
Order By: Relevance
“…Our results revealed that fluctuations in the expression of cytMnSOD were influenced by the molting cycle, and that the highest level of expression was observed during intermolt, suggesting that transcription of this gene may be regulated by ecdysone. Moreover, marked changes in oxygen consumption during the molting cycle may affect MnSOD expression (Engel et al, 2001;Schvezov et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that fluctuations in the expression of cytMnSOD were influenced by the molting cycle, and that the highest level of expression was observed during intermolt, suggesting that transcription of this gene may be regulated by ecdysone. Moreover, marked changes in oxygen consumption during the molting cycle may affect MnSOD expression (Engel et al, 2001;Schvezov et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have examined protein oxidative damage in hemolymph or hemocytes of invertebrates, and most of them analyzed protein carbonylation. For example, increased protein carbonyl concentrations were reported in crabs and mussels in response to seasonal changes and exposure to organic contaminants, metals , and nanoparticles . Protein oxidation in other tissues, including gills and digestive gland, has also been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of ROS displayed different seasonal pattern for small and large lobsters possibly in relation to fluctuations of environmental abiotic and biotic factors within the investigated areas, that were shown to influence the balance between pro-oxidant and antioxidant activity and maintenance of a steady-state ROS level in crustaceans (Liu et al, 2007;Schvezov et al, 2015).…”
Section: °Cmentioning
confidence: 99%